Real-World Multicenter Experience in Tumor Debulking Prior to Blinatumomab Administration in Adult Patients With Relapsed/Refractory B-Cell Precursor Acute Lymphoblastic Leukemia - Bonifacio, Massimiliano; Papayannidis, Cristina; Lussana, Federico; Fracchiolla, Nicola; Annunziata, Mario; Sica, Simona; Delia, Mario; Foà, Robin; Pizzolo, Giovanni; Chiaretti, Sabina (Frontiers in Oncology, 2022)
Blinatumomab is an immunotherapeutic agent with dual specificity for CD3 and CD19 that is approved for the treatment of relapsed/refractory B-cell precursor acute lymphoblastic leukemia (R/R B-ALL). A steroid based pre-treatment is recommended before administering blinatumomab to patients with a high tumor burden to minimize the risk of tumor lysis syndrome, but the optimal debulking regimen and whether it can improve responses remain unclear. The present study retrospectively evaluated real-world outcomes following tumor debulking and blinatumomab infusion in R/R B-ALL adult patients treated at 7 Italian centers. Data were collected from 34 patients. The choice of the cytoreductive therapy was made by the treating clinician on an individual patient basis; regimens included chemotherapy (n=23), steroids (n=7) and tyrosine kinase inhibitors alone or in combination (n=4). The rate of complete responses (CR) and complete minimal residual disease (MRD) responses in CR patients were 67.6% and 81% respectively, after 2 cycles of blinatumomab. Moreover, among patients with a high tumor burden 50% obtained a CR, with 89% of them also achieving a complete MRD response. Favorable responses were also obtained in patients over 50 years of age at treatment initiation. Overall, 7 of 23 patients in CR after blinatumomab underwent hematopoietic stem cell transplantation. The results of this retrospective study highlight the heterogeneity in the use of pre-blinatumomab tumor debulking in real-life clinical practice. Nonetheless, debulking pre-treatment enhanced responses to blinatumomab compared to historic studies, indicating that this strategy may help to improve outcomes for R/R B-ALL patients.